2011
DOI: 10.1016/j.schres.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy of limbic structures displays metabolite differences in young unaffected relatives of schizophrenia probands

Abstract: Imaging studies of schizophrenia patients showed fronto-temporal brain volume deficits, while magnetic resonance spectroscopy (MRS) studies of patients and unaffected biological relatives have found a decrement of the neuronal marker N-acetyl-aspartate (NAA) in the hippocampus and frontal lobes, and increased choline-containing phospholipids. Using a 3 T MR scanner, we determined the metabolite profile within limbic regions (anterior cingulate cortex (ACC) and left hippocampus) of 36 unaffected, adolescent/you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…In general, second-degree biological relatives performed better than their first-degree counterparts, and were more similar to HC in relational memory performance. These observations are consistent with a previous finding by our group (Capizzano et al, 2011); where we found that first-degree relatives of schizophrenia patients had more severe abnormal magnetic resonance spectroscopy (MRS) metabolite levels in limbic brain regions than second-degree relatives. Thus, our current study provides additional evidence that deviations in endophenotypic features of schizophrenia among unaffected biological relatives increase with greater familial proximity to the schizophrenia proband.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, second-degree biological relatives performed better than their first-degree counterparts, and were more similar to HC in relational memory performance. These observations are consistent with a previous finding by our group (Capizzano et al, 2011); where we found that first-degree relatives of schizophrenia patients had more severe abnormal magnetic resonance spectroscopy (MRS) metabolite levels in limbic brain regions than second-degree relatives. Thus, our current study provides additional evidence that deviations in endophenotypic features of schizophrenia among unaffected biological relatives increase with greater familial proximity to the schizophrenia proband.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies have reported similar, but less severe neurocognitive, neuroanatomical, electrophysiological and behavioral abnormalities in non-psychotic biological relatives of schizophrenia patients (Boos, Aleman, Cahn, Pol, & Kahn, 2007; Capizzano, Toscano, & Ho, 2011; Ho, 2007; Ho & Magnotta, 2010; Keshavan et al, 2002; Lawrie et al, 1999; McDonald et al, 2004; Steel et al, 2002). Such intermediate phenotypes are likely related to genetic vulnerability factors that biological relatives have in common with schizophrenia patients.…”
Section: Introductionmentioning
confidence: 87%
“…Metabolite alterations have also been observed in other brain regions in CHR-P and other (i.e. familial) high-risk groups, such as reduced N-acetylaspartate in the thalamus Tandon et al, 2013;Yoo et al, 2009), ACC (Capizzano et al, 2011;Jessen et al, 2006), and caudate (Keshavan et al, 2009)-although increases are also observed in the caudate (de la Fuente-Sandoval et al, 2011). Increased Glx has been reported in the thalamus and caudate, as well as increased (de la or decreased (Menschikov et al, 2016) medial prefrontal GABA-although differences are not always found (Modinos et al, 2018b;Wang et al, 2016).…”
Section: <Figure 1>mentioning
confidence: 98%
“…In a later report, HR subjects showed NAA, PCr + Cr, and GPC + PC reductions in the caudate, and NAA increases in PFC white matter [Keshavan et al, ]. In the Iowa HRS, HR had reduced NAA/Cho ratios for both the left hippocampus and ACC and increased left hippocampus Cho/Cr ratio compared to controls [Capizzano et al, ]. Greater familial proximity to SZ probands among HR was associated with stepwise lowering of NAA/Cho and elevations in Cho/Cr ratios.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%